From Story Time to School: Examining Rwandan Children’s First Encounter with the Rwandan Genocide - Froehlke, Sarah C. (Tufts Archival Research Center, 2023)
This paper aims to provide a starting point to understand when Rwandan children first learn and interact with the history of the Rwandan genocide.; Submitted in partial fulfillment of the degree Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy.; Submitted to the Fletcher School of Law and Diplomacy.